Self-organized learning environment teaching strategy for ELT in Merdeka Belajar concept for high school students in Indonesia - Anis, Muhammad; Anwar, Choiril (Universitas Muhammadiyah Sidoarjo, 2020)
As the development of the industrial revolution takes place, disruptions are happening constantly in almost every major sector of the current industries. Companies and organizations complained about the competencies of the graduates entering the work force. This matter questions the readiness of the education system in preparing the students for the real world. Problems in education such as the regulations, strict policies and instructions from the government are undermining the role of the teachers to do what they think best for their students. This standardization has harmed the motivation and enthusiasm to learn, especially in English language class. Lack of motivation and English Language competency could harm students’ opportunity in accessing the vast global network of knowledge. Merdeka Belajar and SOLE are the promising alternatives in improving ELT. This article is somewhat a position paper trying to clear one side of a debatable opinion about a hot issue. It aims to persuade the reader that our opinion is valid and defensible. In doing so, we then separate the discussion into several parts regarding the analysis of concepts of Merdeka Belajar and SOLE (Self-Organized Learning Environment) related to ELT and motivation in language learning, as well as innovation in education. HIGHLIGHTS: SOLE (Self-Organized Learning Environment) is a concept developed by Sugata Mitra, and the researchers at the SOLE Centre in Newcastle University. SOLE with its highly influenced Constructivism approach lets the learners to take steer of their learning process gives them the ability to make meaning of the subject on their own. Merdeka Belajar (Freedom to Learn) is a new concept that needs to be tread carefully to direct the discussion objectively.